The Prevalence of Malignancy in Appendectomy Specimens for Patients Presenting with Acute Appendicitis: A Systematic Review and Meta-Analysis Protocol - Noruzi, Omid; Mohammad Akhavan, Amir; Rahimi Tanyani, Saman; Abbaszadeh, Mohammad; Halimi, Aram; Keramatinia, Aliasghar; Jarrahi, Alireza Mosavi (Asian Pacific Journal of Cancer Nursing, 2026)
Background: Acute appendicitis is a common emergency, and appendectomy is often performed, yet a subset of specimens contains unsuspected primary or secondary malignancies with implications for nonoperative management strategies. Objectives: The review will estimate the pooled prevalence of histologically confirmed malignancy (primary appendiceal and relevant colorectal or intra abdominal cancers) in appendectomy specimens from adults with acute appendicitis and explore variation by demographics, clinical/imaging features, tumor subtype, and place/time. Methods: Following PRISMA P, English language observational studies (2010 onward) from the three biomedical databases will be screened by two independent reviewers, with standardized data extraction and Joanna Briggs Institute risk of bias assessment. Prevalence will be pooled using random effects meta analysis of transformed proportions, with heterogeneity, subgroup/sensitivity analyses, and, where available, meta analysis of odds ratios for risk factors; publication bias will be examined in larger evidence sets. Ethical considerations: This systematic review and meta analysis will use data extracted exclusively from previously published studies and will not involve direct contact with human participants, collection of identifiable personal data, or any intervention beyond secondary analysis of aggregated results. Consequently, formal approval from an institutional review board or research ethics committee is generally not required.